PERILAKU KOMUNIKASI MASYARAKAT HINDU DAN ISLAM DALAM MENJAGA TOLERANSI UMAT BERAGAMA DI DESA CANDIKUNING (STUDI PASCA NYEPI TAHUN BARU SAKA 1938/2016) - Renata Lusilaora Siringo Ringo; I Wayan Wastawa; I Nyoman Yoga Segara (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This study aims to determine several supporting factors as well as inhibiting communication behavior in Candikuning Village in maintaining tolerance, how communication behavior and to determine the implications of the communication behavior of Hindu and Muslim communities in Candikuning Village in maintaining tolerance. This research is descriptive qualitative research. The research subjects were Hindu and Muslim communities in the village of Candikuning. Data collection methods used were observation, interviews, documentation, and Islam in Candikuning to maintain tolerance supported by historical factors, language, familial attitudes, polite attitudes, and respect for differences. The problems that occur in building tolerance between Hindus and Muslims occur when someone changes religions when they are getting married, there are residents who are not native to Candikuning Village who try to invite people to change beliefs and the language factor. The communication behavior of the Hindu and Muslim communities in Candikuning Village cannot be separated from interpersonal communication activities. Every person's response to a stimulus is always manifested in the form of real or open action, through language, discussion, and dialogue. The nonverbal behavior of the community in Candikuning Village is based on observations using body language and objects. The implications that occur from the communication behavior of the Hindu and Muslim communities in Candikuning Village are the realization of tolerance through the adaptation of community interactions, the reactivation of religious communication forums, and further strengthening of social control.